2004
DOI: 10.1021/om040011r
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Zirconium Complexes with Bianiline-Based N4-Donor Ligands

Abstract: Syntheses of new tetradentate ligands, containing a bianiline backbone and two additional heterocyclic N-donors, and of chiral zirconium complexes containing these ligands as dianions are reported. Crystal structures of some of these complexes show a preference for coordinating the two remaining ligands in a trans- rather than cis-orientation. Nevertheless, these complexes are moderately active in MAO-activated olefin polymerization in toluene solution at 50 °C. With propene, partly isotactic polypropene (55% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…The wide bond angle Cl-Zr-Cl of complex 1 is the result of tridentate ligand, there is few example with wide angle for ethylene polymerization [25]. In any case, it is found that the activity of complex 1 is much higher than that of complex 2, which can be attributed to complex 2 bearing only one chloro ligand [14,26].…”
mentioning
confidence: 92%
“…The wide bond angle Cl-Zr-Cl of complex 1 is the result of tridentate ligand, there is few example with wide angle for ethylene polymerization [25]. In any case, it is found that the activity of complex 1 is much higher than that of complex 2, which can be attributed to complex 2 bearing only one chloro ligand [14,26].…”
mentioning
confidence: 92%
“…The wide bond angle of Cl-Zr-Cl of zirconium complex is the result of tridentate ligand, and there are examples with wide bond angles for ethylene polymerization. 34 The activity depends strongly on the substituent attached to the Cp ligand or Schiff base ligand. The catalytic activity (1) 2.5064(9) Zr-C(3) 2.536(4) Zr-Cl (2) 2.5090(10) Zr-C(4) 2.520(4) Zr-N (1) 2.341(3) Zr-C(5) 2.520(4) Cl(1)-Zr-Cl (2) 151 increased in the order 5 < 3 < 6 < 2 < 4 < 1 under the same conditions.…”
Section: Ethylene Polymerization and Ethylene/1-hexene Copolymerizationmentioning
confidence: 99%
“…Brintzinger and co-workers [27] reported the preparation of diimino-dipyrrole ligand 40c with a chiral 6,6 0 -dimethyl-bianiline backbone and prepared its zirconium complex, (diimino-dipyrrolyl)ZrCl 2 (thf) (42c) (Eq. (12)).…”
Section: Tetradentate Diimino-dipyrrolyl Complexesmentioning
confidence: 99%